Cross-cultural validation and measurement invariance of anxiety and depression symptoms: A study of the Brief Symptom Inventory (BSI) in 42 countries - Quintana, Gonzalo R; Ponce, Fernando P; Escudero-Pastén, Javier I; Santibáñez-Palma, Juan F; Nagy, Léna; Koós, Mónika; Kraus, Shane W; Demetrovics, Zsolt; Potenza, Marc N; Ballester-Arnal, Rafael; Batthyány, Dominik; Bergeron, Sophie; et al. (Journal of affective disorders, 2024)
BACKGROUND: Depression and anxiety are among the most prevalent mental health issues experienced worldwide. However, whereas cross-cultural studies utilize psychometrically valid and reliable scales, fewer can meaningfully compare these conditions across different groups. To address this gap, the current study aimed to psychometrically assess the Brief Symptomatology Index (BSI) in 42 countries. METHODS: Using data from the International Sex Survey (N = 82,243; Mage = 32.39; SDage = 12.52; women: n = 46,874; 57 %), we examined the reliability of depression and anxiety symptom scores of the BSI-18, as well as evaluated evidence of construct, invariance, and criterion-related validity in predicting clinically relevant variables across countries, languages, genders, and sexual orientations. RESULTS: Results corroborated an invariant, two-factor structure across all groups tested, exhibiting excellent reliability estimates for both subscales. The 'caseness' criterion effectively discriminated among those at low and high risk of depression and anxiety, yielding differential effects on the clinical criteria examined. LIMITATIONS: The predictive validation was not made against a clinical diagnosis, and the full BSI-18 scale was not examined (excluding the somatization sub-dimension), limiting the validation scope of the BSI-18. Finally, the study was conducted online, mainly by advertisements through social media, ultimately skewing our sample towards women, younger, and highly educated populations. CONCLUSIONS: The results support that the BSI-12 is a valid and reliable assessment tool for assessing depression and anxiety symptoms across countries, languages, genders, and sexual orientations. Further, its caseness criterion can discriminate well between participants at high and low risk of depression and anxiety.
Keywords: dospělí; průzkumy a dotazníky; Female; Psychometrics; dítě; psychometrie; srovnání kultur; úzkost; Adult; ženské pohlaví; Surveys and Questionnaires; Reproducibility of Results; lidé; Anxiety; reprodukovatelnost výsledků; Male; Cross-Cultural Comparison; Child; deprese; mužské pohlaví; Depression; Humans